Pier shape and alignment effects on local scour - Fael, Cristina (2017)
Bridge piers may have several horizontal shapes and be built with different alignment angles towards the flow direction. The effects of pier shape and alignment have been studied by only a few researchers, the most well-known being Laursen and Toch [1956]. In the present study, 55 long-duration laboratory tests were run under steady, clearwater flow close to the threshold for initiation of sediment motion, to address the effect of shape and skew-angle on the equilibrium scour depth. Five different pier shapes were considered: circular, rectangular square-nose, rectangular round-nose, oblong and piles group; the tested skew-angles were 0, 30, 45, 60, and 90°. Relevant contributions were achieved on the effect of shape at skewed piers and performance of the equation suggested by Richardson and Davis [2001] to account for the pier alignment factor.